Pengaruh Kepercayaan dan Kemudahan terhadap Keputusan UMKM dalam Pembiayaan Peer to Peer Lending di Kota Depok - Efriyanto, Efriyanto; Aminah, Aminah (STIE Indonesia Banking School, 2023)
The Financial Technology Association (AFTECH) in Indonesia reported that there are still 49 million Small and Medium Enterprises (SME) whose poor people have not received support from banks due to too heavy regulations and inclusion of conditions for guarantees. Peer to Peer Lending can help business actors or borrowers who need assets by providing unsecured credit. The purpose of this study is to determine whether the Trust and Convenience factor can influence SME decisions in financing through peer-to-peer lending applications. This study uses primary data by interviewing SME actors in Depok City and distributing questionnaires online and offline and has obtained 100 respondents. With the criteria of respondents who have business credit loans on fintech lending platforms (online loans) that are registered and licensed at OJK, have SME, domiciled in Depok City, aged 18 years to more than 50 years. Data analysis in this study used multiple linear regression analysis. It was found that the Trust and Convenience factor had a significant effect on SME decisions in financing through peer-to-peer lending in Depok.